The writer and the terrorist: on Michel Houellebecq. Issue 9 (1st September 2020) - Williams, Russell
ABSTRACT: This essay attempts to bring the politics of anti-humanism up to date with the late twentieth and early twenty-first centuries by juxtaposing the humanistic figure of the realist writer with the anti-humanism of the terrorist, a figure that is pervasive in late twentieth century fiction. A prominent public intellectual in his native France, since the atrocities of 9/11 and the 2015 Charlie Hebdo attacks Houellebecq has been inextricably associated with terrorism and this essay attempts to establish why. Looking both inside and outside his writing, it suggests ways in which Houellebecq has been used by discourses of power to construct terrorism as a political reality. It also considers how far the author himself has played a knowing role in this process, examining – with reference to fellow contemporary writers Yann Moix, Martin Amis and theorists Guy Debord and Bifo Berardi – signs of his ambiguous sympathy for terroristic impulses. I end by comparing Houellebecq to other novelists who also employ the figure of the terrorist – among them Paul Auster and Don DeLillo – and by illustrating a larger trend in twenty first century literature towards the radical reworking of a Romantic association between writing and terror.